Acute Respiratory Failure Due to Vaping-Induced Lung Injury: A Case Report and Management Review - Urlapu, Kinnera Sahithi; Venkatram, Sindhaghatta; Soliman, Maryam; Ronderos, Diana; Diaz-Fuentes, Gilda (International Journal of Innovative Research in Medical Science, 2023)
Awareness of the detrimental effects of vaping on the respiratory system has significantly increased in the last few years. In July 2019 the Wisconsin Department of Health Services and the Illinois Department of Public Health established the definitions for e-cigarette or vaping product use-associated lung injury (EVALI); it was mostly attributed to the flavoring agents containing vitamin E acetate which in the aerosol form causes surfactant dysfunction. The diagnosis and management of severe EVALI still remain a challenge as the presentation can be easily confused with many other respiratory conditions. There are no guidelines regarding the management of those patients and outcomes vary from total resolution to development of chronic lung disease. We present a patient with EVALI and acute respiratory distress syndrome (ARDS) that was successfully treated with steroids.